Learning styles and their relationship with preferred teaching methodologies and academic achievement among medical students in teaching medical college, Tamil Nadu - Tamilarasan Muniyapillai; Karthikeyan Kulothungan; Shagirunisha Rizvana Abdul Malik; Shekshi Janet Jeevaraj; Shrimathi Ashokan; Sindhurajeswari Ravichandran; Sivaranjani Ambalavanan; Sowmiya Jayaraman (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Learning styles for medical students have been studied worldwide, and instructors must know and employ the best methods to help students learn. This study evaluates undergraduate medical students' learning styles, preferred teaching methods, and academic examination scores. MATERIALS AND METHODS: From January to December 2022, this cross-sectional study was performed with medical students at a teaching hospital in Perambalur, Tamil Nadu, India. About 421 individuals were selected using a probability-proportionate size sampling method. A semi-structured pro forma was used to collect the socio-demographic profile, VARK model learning style questionnaire, and teaching method preferences. The data were analyzed using SPSS-21, and the categorical data were represented as frequency and percentage, whereas mean and standard deviation represent quantitative data. The Chi-square test was used to investigate the relationship between academic performance and teaching approaches to the preferred learning style. RESULTS: Kinesthetic learning was the preferred sensory modality. Nearly 61.8% of medical students were female. The most common preferred learning style among them was (36.8%) kinesthetic, followed by (36.1%) auditory. Most of them received good academic results (64.8%), followed by average (21.9%) results. Most of the students had chosen a demonstration (81.2%), followed by an interactive lecture (77.2%), as their preferred teaching method. There is a significant association of learning style with participant age (p 0.007), year of study (p 0.0001), and preferred teaching methodologies like a demonstration, small group discussion, self-presentation, and laboratory work, which is statistically significant. There is no association between learning style and academic performance. CONCLUSION: Different teaching approaches, such as demonstration, small-group discussion, self-presentation, and laboratory work, were related to the various learning styles of the students. We also determined that the individuals' preferred learning styles do not affect their academic achievement.